Expanding the applications of the combined transverse upper gracilis and profunda artery perforator (TUGPAP) flap for extensive defects. Issue 4 (17th December 2018) - Ciudad, Pedro; Huang, Tony Chieh‐Ting; Manrique, Oscar J.; Agko, Mouchammed; Sapountzis, Stamatis; Nicoli, Fabio; Diya Sabbagh, M.; Pont, Luis Parra; Moran, Steven L.; Chen, Hung‐Chi
Abstract : Background: The medial thigh is a well‐hidden area. The two most common flaps from this area are the transverse upper gracilis (TUG) and profunda artery perforator (PAP) flaps. Herein, we explored the applications of combined TUGPAP flap to reconstruct large and complex defects in different regions. Methods: Between November 2015 and May 2017, 28 patients who underwent reconstruction and extensive soft tissue coverage with the TUGPAP flap for the breasts, head and neck, and pelvi‐perineal regions were included. The defects size ranged from 22 to 29 × 6–8 cm. All flaps were based on the two pedicles: the medial circumflex femoral artery for TUG flap and the profunda artery perforator for PAP flap. They were each anastomosed to a set of recipient vessels. A "Y"‐shaped interposition vein graft (YVG) was used if only one recipient artery was available. Results: The harvested skin paddle had dimensions ranged from 20 to 30 × 6–9 cm and all flaps survived completely. Postoperative complications included one case each of donor and recipient site seroma, and one case of wound dehiscence. They were all successfully managed conservatively. During an average follow‐up period of 12.7 months, one patient reported permanent paresthesia in the donor site and another developed hypertrophic scar. All patients were able to resume daily activity without major concerns. Conclusion: The combined TUGPAP flap is a safe, effective, and a good alternative to the common workhorse flaps as it offers the potential for a large skin paddle and decent soft tissue volume with low donor site morbidity in a well‐concealed area.